PENGARUH WORD OF MOUTH DAN INFLUENCER MARKETING TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK SKINCARE GLAD2GLOW DI KAPUPATEN KOLAKA - Sania Sania; Muhammad Stiadi; Agus Zulbay (Jurnal Daya Saing, 2026)
This study aims to determine the effect of word of mouth and influencer marketing on purchasing decisions of Glad2Glow skincare products in Kolaka Regency. The research method used is a quantitative approach with Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The population in this study consists of people in Kolaka Regency, with a sample of 120 respondents selected using purposive sampling technique. Data were collected through questionnaires. The results show that word of mouth has a positive and significant effect on purchasing decisions. This indicates that recommendations, shared experiences, and communication among consumers play an important role in influencing purchasing decisions. In addition, influencer marketing also has a positive and significant effect on purchasing decisions, meaning that influencers’ credibility, attractiveness, and ability to deliver information can influence consumers in choosing products. Simultaneously, both variables contribute significantly to purchasing decisions. Therefore, it can be concluded that word of mouth and influencer marketing are important factors in increasing consumer purchasing decisions toward Glad2Glow skincare products in Kolaka Regency..